KARAKTERISTIK EKSTRAK PEWARNA ALAMI BUGENVIL (Bougainvillea x buttianaâ€œmaharaâ€) PADA PERLAKUAN JENIS PELARUT DAN SUHU EKSTRAKSI - Vonny Tanone; Ni Made Wartini; Luh Putu Wrasiati (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2023)
This research aims to determine the effect of solvent types and extraction temperatures on the characteristics of natural dyes of bougainvillea, determine of the solvent type and extraction temperature which can produce natural dyes from bougainvillea with the best characteristics, and identify organic compounds that makeup bougainvillea dye extract from the best treatment. This study used a factorial randomized block design with 2 factors. Factor I is a solvent type consisting of 3 levels: ethanol 96%, ethanol 96%: citric acid 20% (1:1), and citric acid 20%. Factor II is extraction temperature consisting of 3 levels: 30oC, 45oC, and 60oC. The results showed that the treatment of extraction temperature, solvent type, and interaction had an effect on betacyanin capacity, yield, acidity (pH), brightness (L *), redness (a *), and yellowish level (b *). The treatment of ethanol 96% solvent: citric acid 20% with extraction temperature of 30oC was the best treatment for obtaining bougainvillea dye extract with characteristics of betacyanin capacity 413.545 mg/100g, yields of 9,450%, pH 0.835, value of L* 4,335, values of a* 1,740 and value of b* 33,770. Organic compounds that comprised bougainvillea extract from the best treatment were betanidin quinone, betanin, and dicarboxylic derivatives.